Theorizing Best Practices for Preventing Sexual Assaults in Higher Education: Adult Educators' Perspectives - Amber Giffin; Mitsunori Misawa (Adult Education Research Conference, 2018)
This paper analyzes the literature regarding universities’ sexual assault prevention programs in an effort to identify best practices for reducing the number of sexual assaults on university campuses.
Keywords: adult education; sexual assault prevention; higher education